Hepatocyte permissiveness to Plasmodium infection is conveyed by a short and structurally conserved region of the CD81 large extracellular domain. - Samir Yalaoui (Public Library of Science (PLoS), 2008)
Invasion of hepatocytes by Plasmodium sporozoites is a prerequisite for establishment of a malaria infection, and thus represents an attractive target for anti-malarial interventions. Still, the molecular mechanisms underlying sporozoite invasion are largely unknown. We have previously reported that the tetraspanin CD81, a known receptor for the hepatitis C virus (HCV), is required on hepatocytes for infection by sporozoites of several Plasmodium species. Here we have characterized CD81 molecular determinants required for infection of hepatocytic cells by P. yoelii sporozoites. Using CD9/CD81 chimeras, we have identified in CD81 a 21 amino acid stretch located in a domain structurally conserved in the large extracellular loop of tetraspanins, which is sufficient in an otherwise CD9 background to confer susceptibility to P. yoelii infection. By site-directed mutagenesis, we have demonstrated the key role of a solvent-exposed region around residue D137 within this domain. A mAb that requires this region for optimal binding did not block infection, in contrast to other CD81 mAbs. This study has uncovered a new functionally important region of CD81, independent of HCV E2 envelope protein binding domain, and further suggests that CD81 may not interact directly with a parasite ligand during Plasmodium infection, but instead may regulate the function of a yet unknown partner protein.